Kinetic and equilibrium study of graphene and copper oxides modified nanocomposites for metal ions adsorption from binary metal aqueous solution - Ali, Alaa H.; Kareem, Asmaa Bahjat; Al-Rawi, Usama A.; Khalid, Ushna; Zhang, Shengfu; Zafar, Fatima; Papraćanin, Edisa; Hatshan, Mohammad Rafe; Sher, Farooq (Frontiers in Chemistry, 2023)
These days, the main cause of pollution of natural water resources is heavy metal ions. The metal ions removal such as nickel (Ni2+) and cadmium (Cd2+) has been given considerable attention due to their health and environmental risks. In this regard, for wastewater treatment containing heavy metal ions, graphene oxide (GO) nanocomposites with metal oxide nanoparticles (NPs) attained significant importance. In this study, the graphene oxide stacked with copper oxide nanocomposites (GO/CuO-NCs) were synthesized and characterized by using FTIR, XRD, SEM, EDX and AFM analytical procedures. The prepared GO/CuO-NCs were applied for the Ni2+ and Cd2+ ions removal from a binary metal ions system in batch and continuous experiments. The obtained results revealed that the GO/CuO-NCs exhibited the highest removal efficiencies of Ni2+ (89.60 ± 2.12 %) and Cd2+ (97.10 ± 1.91%) at the optimum values of pH: 8, dose: 0.25 g, contact time: 60 min and at 50 ppm initial metal ions concentration in a batch study. While 4 mL/min flow rate, 50 ppm initial concentration and 2 cm bed height were proved to be the suitable conditions for metal ions adsorption in the column study. The kinetic adsorption data exhibited the best fitting with the pseudo 2nd order model. While the adsorption isotherm provided the best-fitting data in Langmuir isotherm model. This study suggested that the GO/CuO nanocomposites have proved to be efficient adsorbents for Ni2+ and Cd2+ ions from a binary metal system.